(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3HJhSWg dgG hjchf PcQg Ydi gPg GdMGd CTcd hCdjb, bGd eDda gPG GdcJGH, hdYd HYV ef jJUaM Pdc jfcQ JQcfG JUfjag CHhGHkG Ydi WQGFb GdZfGA hYdi WHbGJ GdeZfjf aj CReGfge heQGJHge s
(3BNQgG (B:s
(3bGd NGdO GHf Lejd MOKfj QLGd ef Hfj YGeQ Cf RhL djdi hCHGgG NQLG aj CeQ WQb GdMj Edi ecI aCQSdJ HCeI dgG Edi GdLfhf aOYJg aCbGe YfOgG djdi hCNQLJg aj GdSMQ s
(3ef fSNI SGOSIs
(3hQO CjVkG JMJ Qbe (B2176s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B44 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B129s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs